2020
DOI: 10.3390/antibiotics9120910
|View full text |Cite
|
Sign up to set email alerts
|

Actinobacillus pleuropneumoniae Eradication with Enrofloxacin May Lead to Dissemination and Long-Term Persistence of Quinolone Resistant Escherichia coli in Pig Herds

Abstract: Norway has a favourable situation with regard to health status and antimicrobial usage in the pig production sector. However, one of the major disease-causing agents in the commercial pig population is Actinobacillus pleuropneumoniae (APP). In some herds, APP eradication has been performed by using enrofloxacin in combination with a partial herd depopulation. The aim of this study was to investigate the long-term effects of a single treatment event with enrofloxacin on the occurrence of quinolone resistant Esc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…A recent study by Janssen et al indicated that the use of enrofloxacin may affect the development of the resistance of commensal E. coli strains in pigs [ 76 ]. Analogous results were obtained by Lin et al, who noted an increase in the number of ciprofloxacin-resistant E. coli strains in pigs treated with enrofloxacin [ 77 ], and Kaspersen et al, who found that even a single treatment with enrofloxacin significantly increased the probability of developing quinolone resistance in commensal E. coli strains [ 78 ]. Pomorska-Mól et al also observed that the use of enrofloxacin at the time of vaccination for Aujeszky’s disease significantly delayed the humoral response and decreased the level of IFN-γ in pigs [ 79 ].…”
Section: Efficacy Of Enrofloxacin In Veterinary Medicinesupporting
confidence: 71%
“…A recent study by Janssen et al indicated that the use of enrofloxacin may affect the development of the resistance of commensal E. coli strains in pigs [ 76 ]. Analogous results were obtained by Lin et al, who noted an increase in the number of ciprofloxacin-resistant E. coli strains in pigs treated with enrofloxacin [ 77 ], and Kaspersen et al, who found that even a single treatment with enrofloxacin significantly increased the probability of developing quinolone resistance in commensal E. coli strains [ 78 ]. Pomorska-Mól et al also observed that the use of enrofloxacin at the time of vaccination for Aujeszky’s disease significantly delayed the humoral response and decreased the level of IFN-γ in pigs [ 79 ].…”
Section: Efficacy Of Enrofloxacin In Veterinary Medicinesupporting
confidence: 71%
“…This antimicrobial has been used off-label in Quebec since the 2000s. In addition, fluoroquinolone non-susceptibility in E. coli isolated from diseased pigs has been observed in other countries [17,18] and has been associated with enrofloxacin treatment previously in herds [19]. Moreover, clonality has been demonstrated among ETEC isolates causing disease in pigs in the USA [20].…”
Section: Introductionmentioning
confidence: 96%
“…The susceptibility of bacteria to enrofloxacin is important at both the public health and pig health levels, as it is still commonly used in most countries, despite its public health importance being as high as that of colistin [ 14 , 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%